1983
DOI: 10.1128/mcb.3.8.1371
|View full text |Cite
|
Sign up to set email alerts
|

Methylation and rearrangement of mouse intracisternal a particle genes in development, aging, and myeloma.

Abstract: Sequences of DNA that hybridize on Southern blots with cloned intracisternal A-particle (IAP) sequences have been examined in genomic DNAs of neonatal mice, livers of adult mice (3, 6, 12, 18, 24, and 26 months old), and the solid myeloma tumor MOPC-315. The isoschizomers HpaII (CCGG or mCCGG) and MspI (CCGG or C'mCGG) were used to assess methylation. All the DNAs produced a major 0.5-kilobase MspI fragment that hybridizes with IAP probe. Only the myeloma DNA, and to a much lesser degree DNA from senescent mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…In the latter case, activation of transposable elements and endogenous retroviruses have been invoked and in some cases documented (35,36) as a possible event participating in somatic mutations. Along the same line, demethylation upon aging of the LINE murine mobile elements (and to some extent of the IAPs) has been reported (37,38). In fact, the present study (see also Refs.…”
Section: An Evolutionarily Conserved Orf With Similarity To the Yeastmentioning
confidence: 54%
“…In the latter case, activation of transposable elements and endogenous retroviruses have been invoked and in some cases documented (35,36) as a possible event participating in somatic mutations. Along the same line, demethylation upon aging of the LINE murine mobile elements (and to some extent of the IAPs) has been reported (37,38). In fact, the present study (see also Refs.…”
Section: An Evolutionarily Conserved Orf With Similarity To the Yeastmentioning
confidence: 54%
“…There is some evidence that DNA methylation declines with age in vivo. Romanov and Vanyushin have demonstrated decreases in the methylation of reiterated, but not unique, sequences in cattle with ageing (24) whilst Mays-Hoopes et al have observed hypomethylation of specific moderately repeated sequences of the mouse liver genome with age (18). It is known that reiterated DNA sequences tend to have a higher proportion of methylated sites than other areas of the genome (21) and experiments are under way to look at keratinocyte reiterated DNA sequences in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we have used a two-dimensional (2-D) gel electrophoresis technique to detect 1AP elements that are hypomethylated in their 5' long terminal repeats (LTRs). This approach is based on the observed correlation between the extent of 1AP proviral hypomethylation and the level of IAP expression in a number of cell lines (13)(14)(15)(16) (20 mA). By using a pulse controller (Hoefer PC750), the current was periodically reversed at a constant 3:1 ratio between the forward and reverse intervals; the reverse interval varied from 150 msec initially to 345 msec.…”
Section: Introductionmentioning
confidence: 99%